Intergenerational Politics in an Aging Society: The Graying of Japanese Voters - Takao, Yasuo (University of California Press, 2022)
Japan’s population is aging faster than any other nation’s, producing many more older voters, and raising an important question related to intergenerational equity. Do older voters prioritize their short-term self-interest at the expense of other generations? I find that the older voters in Japan are surprisingly less self-interested—even less than similarly aged voters in other advanced economies—in maximizing their benefits as service consumers to the detriment of younger voters. This behavior of older voters in Japan is an enigma. To stimulate dialogue about an equitable and sustainable welfare system, I consider a set of structural and institutional factors that may, individually or collectively, help explain the apparently less self-interested preferences of older voters in Japan.